(untitled) (Research, Society and Development, 2022)
Lifestyle is a set of beliefs, values and attitudes which are reflections of our daily habits, that is, our patterns of behaviour. Taking into account that Physical Education, as a mandatory curricular component in the basic education level, is essential for the guiding of posture and healthy habits, it is expected of the Physical Education teacher to be an example in this aspect. Therefore, several studies aimed to analyse the profile of Physical Education teachers regarding their own health habits, such as the ones as described by Both, Nascimento, Borgatto, Silva, Barros, Hartwig, Rombaldi, Jorgi and Ramalho. Thus, this article objective was to analyse the physical education teachers lifestyle in Canindé – CE, in 2019. For this purpose, we utilized a descriptive field research, quantitative and cross-sectional. The sample was consisted of 12 Physical Education teachers of the state teaching network in Canindé-CE, 8 women and 4 men, which answered the questionnaire ‘‘Pentáculo do Bem-Estar’’ (PBE) – “Well-being Pentacle” - as suggested by Nahas, Barros and Francalacci (2000) in order to evaluate people’s lifestyle. The results showed the predominance of a healthy lifestyle on most of Physical Education teachers, but also a diminution of physical activity habit throughout their time when working professionally.